2015
DOI: 10.1097/nnr.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Contributors to Metabolic Syndrome

Abstract: There is a need for large-scale, longitudinal, and interventional studies to evaluate and alter these potential risk factors, thus reducing MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(40 reference statements)
1
2
1
2
Order By: Relevance
“…Although our findings demonstrated that physical activity significantly decreased the risk of MetS only in young adult males, our ability to determine causality is limited due to the cross-sectional study design. Our findings are, however, consistent with those of a previous study (Saylor & Friedmann, 2015), which indicated that physical activity is associated with a lower risk of developing MetS. In one study, males exhibited significantly larger improvements in insulin sensitivity than did females following an exercise-training program in the absence of substantial weight loss (Boulé et al, 2005).…”
Section: Unhealthy Lifestyle Behaviors Associated With the Risk Of Mesupporting
confidence: 92%
“…Although our findings demonstrated that physical activity significantly decreased the risk of MetS only in young adult males, our ability to determine causality is limited due to the cross-sectional study design. Our findings are, however, consistent with those of a previous study (Saylor & Friedmann, 2015), which indicated that physical activity is associated with a lower risk of developing MetS. In one study, males exhibited significantly larger improvements in insulin sensitivity than did females following an exercise-training program in the absence of substantial weight loss (Boulé et al, 2005).…”
Section: Unhealthy Lifestyle Behaviors Associated With the Risk Of Mesupporting
confidence: 92%
“…for men; (2) Fasting blood glucose ≥ 100 mg/dL; (3) Serum triglycerides ≥ 150 mg/dL; (4) Blood pressure ≥ 135/85 mm Hg; and (5) HDL (“good”) cholesterol < 40 mg/dL for men or < 50 mg/dL for women. MetS was defined as an individual has three or more risk factors (Saylor and Friedmann, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Individuals with MetS are also at increased risk of morbidity and mortality from stroke, and myocardial infarction compared to those without the syndrome (Kaur, 2014). In the United States, the number of individuals diagnosed with MetS rose from 47 million in 2000 to 76 million in 2009 with only a slight decrease in 2010 (Saylor and Friedmann, 2015). From 2011 to 2012, the overall prevalence of MetS stood at 34.7% of the US population with the greatest burden in those 60 years and older (Aguilar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…inszomnia, alvási apnoe szindróma, narkolepszia vagy nyugtalan láb szindróma stb. (7,8). Az alvás az életben maradáshoz nélkülözhetetlen szükséglet a szervezet számára (4,9).…”
Section: Az Alvásról éS Alvászavarokrólunclassified